Abhinaya Circuit Video Media in Online Learning to Train Physical-Motor Ability of Early Childhood: A Developmental Studies - Ramadhanty, Erfira; Wulandari, Retno Tri; Tirtaningsih, Munaisra Tri (Universitas Nahdlatul Ulama Surabaya, 2022)
This study aims to develop an Abhinaya Circuit video game media suitable for training gross motor skills in early childhood. This research uses Research and Development research. The method applied in this research refers to the Borg and Gall method, which consists of 10 research steps. In this study, only eight steps were applied; (1) conducting a needs analysis, (2) planning, (3) developing a product design at the beginning, (4) validating the developed product design, (5) revising the product design, (6) conduct trials, (7) revise the product (8) Production. The collected data in this study using observation, interview, and documentation techniques. Data analysis in the form of descriptive quantitative. The results of this study were obtained: (1) the feasibility test results of the Abhinaya Circuit video media were carried out by two validators, namely media expert lecturers and early childhood physical-motoric lecturers. The media expert validator research results are 83.6% with valid criteria and can be used with a little revision. The results of the instrument validation of children's motor physicists were 94.6%, with very valid criteria so that they could be used without revision. (2) The results of product trials in terms of 3 aspects of safety, convenience, and attractiveness (zig-zag running, crawling, throwing balls, cranks, shuttle runs) obtained a total percentage of 94.6%, which was included in the feasible category. Based on the results of the research that has been done, it can be concluded that the Abhinaya circuit media is safe, easy and interesting and can be used as an alternative to stimulate gross motor skills in early childhood, especially children aged 4-6 years.